2019
DOI: 10.1177/2329488419856803
|View full text |Cite
|
Sign up to set email alerts
|

Communication Apprehension Across the Career Span

Abstract: Working adults engage in a variety of communication activities for their entire careers. Yet relatively, little has been established regarding whether or how average communication anxiety levels change over time, especially after college. The purpose of this study was to test communication anxiety levels across the career span. Age, levels of work experience, frequency in making presentations, and levels of communication apprehension as measured by the Personal Report of Communication Apprehension (PRCA) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 101 publications
0
11
0
5
Order By: Relevance
“…Previous research used the PRCA-24 to look at levels of CA of participants in the age range of 20 to 72 years. The said research showed the existence of a reduction of CA amongst groups of more mature participants (Marcel, 2019). The sources of evidence in this study were based upon the age range of 19 to 20 years.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Previous research used the PRCA-24 to look at levels of CA of participants in the age range of 20 to 72 years. The said research showed the existence of a reduction of CA amongst groups of more mature participants (Marcel, 2019). The sources of evidence in this study were based upon the age range of 19 to 20 years.…”
Section: Discussionmentioning
confidence: 77%
“…Shortcomings in this research were that the subjects comprised only tertiary students from one faculty of only one tertiary educational institution. Later research may consider the use of participants from a more diverse age group (Marcel, 2019), or diverse ethnic or national groups (Croucher et al, 2019). Other shortcomings were the use of only three sources of evidence, i.e., internal structure, using reliability and the analysis of factors, together with connections to another variable, i.e., assertiveness.…”
Section: Limitations and Suggestionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding suggests that, despite their typically older age and greater work experience, MBA students still would benefit from opportunities to develop their communication skills. Likewise, more frequent presenting among business professionals has been associated with reduced levels of communication apprehension (Marcel, in press), something coursework can be designed to foster.…”
Section: Literature Reviewmentioning
confidence: 99%